Method for evaluating the correlation between densification and corrosion resistance of additively manufactured aluminum alloys
Patent Information
- Application Number
- CN202611140668.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-30
AI Technical Summary
[0006]针对现有技术中合金材料性能评估存在的内部质量检测与耐蚀性能评估相互割裂以及样品个体差异对结果干扰严重的技术问题,本发明提供了一种增材制造铝合金致密度与耐蚀性关联评估方法
(1)本发明采用同一增材制造铝合金试样依次在硫酸钠、氯化钠和氟化钠电解液中进行电化学测试,能够在同一微观结构实体上获取多种腐蚀环境下的响应信息,避免了不同试样之间因组织、孔隙和致密度差异造成的数据波动,提高了测试结果之间的可比性和可靠性。
Smart Images

Figure CN122631725B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys, belonging to the field of material performance characterization and non-destructive testing technology. Background Technology
[0002] Additive manufacturing technology offers great flexibility in the fabrication of complex aluminum alloy components. However, the inherent characteristics of the process result in a microstructure that differs from traditional materials, often containing defects such as porosity and incomplete fusion, leading to fluctuations in material density. Density is a key intrinsic factor affecting the mechanical properties and corrosion resistance of additively manufactured aluminum alloys. Regions with high porosity or low density not only weaken load-bearing capacity but also easily become corrosion initiation points and propagation channels, seriously threatening the long-term service safety of components in harsh environments.
[0003] Currently, the evaluation of the quality and performance of additively manufactured parts mainly relies on two disconnected methods: one is to directly detect internal defects and density through metallographic observation, which is accurate but destructive or invasive, inefficient, and costly, making it difficult to use for batch or online screening; the other is to evaluate corrosion resistance through standard salt spray tests or single-medium electrochemical tests, which reflect the material's "apparent" corrosion resistance but cannot directly attribute performance to specific internal quality indicators such as density. Due to the common microstructural differences among additively manufactured samples, using different samples for density and corrosion testing often masks the correlation between the data obtained by the intrinsic fluctuations of the samples, making it difficult to establish reliable intrinsic performance relationships.
[0004] Electrochemical testing techniques, particularly electrochemical impedance spectroscopy and potentiodynamic polarization, are sensitive methods for studying the corrosion behavior of metals. Existing research largely focuses on testing in a single corrosive environment (such as 3.5% NaCl solution). However, different types of defects in additively manufactured aluminum alloys (such as surface open pores, subcutaneous closed pores, and interlayer incomplete fusion) exhibit varying sensitivities to different corrosion mechanisms. For example, chloride-induced corrosion may be extremely sensitive to surface active sites; while the chemical dissolution of the alumina passivation film by fluoride ions may place higher demands on the overall density and compositional homogeneity of the material. Therefore, test results from a single environment alone cannot fully reflect the complex impact of internal defects (i.e., density level) on the overall corrosion resistance of the material.
[0005] Therefore, there is an urgent need to develop a new evaluation strategy that can use relatively fast, low-destructive testing methods to obtain multidimensional information on the same physical entity, thereby establishing an effective correlation between the internal state of a material and its performance in complex chemical environments. Summary of the Invention
[0006] To address the technical problems in existing alloy material performance evaluation technologies, such as the disconnect between internal quality testing and corrosion resistance assessment, and the significant interference of individual sample differences with the results, this invention provides a method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys. This invention ensures that all subsequent comparative data originate from the same microstructure entity by consistently using the same additively manufactured aluminum alloy sample and subjecting it to a series of electrolyte environment tests with different corrosion mechanisms, thus eliminating the influence of fluctuations between samples.
[0007] To achieve the above objectives, the present invention proposes the following technical solution: A method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys, comprising the following steps: (1) The aluminum alloy sample to be tested in additive manufacturing was packaged and used as the working electrode, which together with the graphite counter electrode and the saturated calomel reference electrode formed a three-electrode system; it was then immersed in sodium sulfate electrolyte, sodium chloride electrolyte, and sodium fluoride electrolyte in sequence; in each electrolyte, open circuit potential monitoring, electrochemical impedance spectroscopy test and potentiodynamic polarization curve test were performed in sequence; after each test, the surface of the working electrode was cleaned and dried; (2) Extract characteristic electrochemical parameters from the test data obtained in step (1) to form a characteristic electrochemical parameter set for the sample. The characteristic electrochemical parameter set includes: the charge transfer resistance R measured in sodium sulfate electrolyte. ct The self-corrosion potential E measured in sodium chloride electrolyte corr Corrosion current density i measured in sodium fluoride electrolyte corr The overall corrosion resistance level of the material represented by the sample is evaluated based on this set of characteristic electrochemical parameters. (3) Based on the comprehensive corrosion resistance grade obtained from the evaluation, further evaluate the density grade of the material represented by the sample. The higher the comprehensive corrosion resistance grade, the higher the density grade and the larger the density value.
[0008] In the above technical solution, in step (2), the characteristic electrochemical parameter set and the overall corrosion resistance have the following quantitative correlation: The charge transfer resistor R ct It is positively correlated with corrosion resistance, i.e., R ct The larger the value, the stronger the corrosion resistance; according to the charge transfer resistance R... ct Corrosion resistance rating: When R ct ≥8.0×10 3 Ω·cm 2 When the corrosion resistance is 5.0 × 10⁻⁶, the corrosion resistance grade is determined to be Grade A; when the corrosion resistance is 5.0 × 10⁻⁶, the corrosion resistance grade is determined to be Grade A. 3 ≤R ct <8.0×10 3 Ω·cm 2 When the corrosion resistance is 2.5 × 10⁻⁶, the corrosion resistance grade is determined to be B; when the corrosion resistance is 2.5 × 10⁻⁶, the corrosion resistance grade is determined to be B.3 ≤R ct <5.0×10 3 Ω·cm 2 When R is present, the corrosion resistance grade is determined to be C; when R is present, the corrosion resistance grade is determined to be C. ct <2.5×10 3 Ω·cm 2 At that time, the corrosion resistance level was determined to be Grade D; The self-corrosion potential E corr It is positively correlated with corrosion resistance, i.e., E corr The higher the positive value, the stronger the corrosion resistance; according to the self-corrosion potential E... corr Corrosion resistance rating: When E corr When the corrosion resistance is ≥-0.80 V, the corrosion resistance grade is determined to be Class A; when -1.05 ≤ E corr When the voltage is less than -0.80 V, the corrosion resistance grade is determined to be B; when -1.20 ≤ E corr When the temperature is < -1.05 V, the corrosion resistance grade is determined to be C; when the temperature is < -1.05 V, the corrosion resistance grade is determined to be C. corr When the voltage is less than -1.20 V, the corrosion resistance grade is determined to be D. The corrosion current density i corr It is negatively correlated with corrosion resistance, i. corr The smaller the value, the stronger the corrosion resistance; according to the corrosion current density i corr Corrosion resistance rating: When i corr ≤25.0 μA·cm -2 When 25 < i, the corrosion resistance grade is determined to be Grade A; when 25 < i corr ≤37 μA·cm -2 When 37 < i, the corrosion resistance grade is determined to be B; corr ≤50 μA·cm -2 When the corrosion resistance is determined to be grade C; when i corr >50 μA·cm -2 At that time, the corrosion resistance level was determined to be Grade D; According to the above R ct E corr and i corr The overall corrosion resistance rating is determined by assessing the three individual ratings according to the following rules: When R ct Grade A, i co rr is grade A, and E corr When the grade is not lower than B, the overall corrosion resistance grade is determined to be A. When the conditions for Grade A are not met, but all three individual grades are not lower than Grade B, the overall corrosion resistance grade is determined to be Grade B. When all three individual grades are not lower than Grade C, and at least one individual grade is Grade C, the overall corrosion resistance grade is determined to be Grade C. When any single item is rated D, the overall corrosion resistance rating is determined to be D. Grade A corresponds to no corrosion on the surface, Grade B corresponds to slight corrosion, Grade C corresponds to moderate corrosion, and Grade D corresponds to severe corrosion.
[0009] Further, in step (3), when the overall corrosion resistance grade is A, the corresponding density grade is A, that is, density ≥ 99.60%; when the overall corrosion resistance grade is B, the corresponding density grade is B, that is, 99.50% ≤ density < 99.60%; when the overall corrosion resistance grade is C, the corresponding density grade is C, 99.00% ≤ density < 99.50%; when the overall corrosion resistance grade is D, the corresponding density grade is D, that is, density < 99.00%.
[0010] Preferably, when R ct ≥8.0×10 3 Ω·cm 2 E corr ≥ 0.80 V, i corr ≤25 μA·cm -2 When the overall corrosion resistance is determined to be Grade A (no visible corrosion); when 5.0×10 3 ≤R ct <8.0×10 3 Ω·cm 2 -1.05≤E corr <-0.80 V, 25<i corr ≤37 μA·cm -2 When the overall corrosion resistance level is determined to be Grade B (slight corrosion); when 2.5×10 3 ≤R ct <5.0×10 3 Ω·cm 2 -1.20≤E corr <-1.05 V, 37<i corr ≤50 μA·cm -2 When the overall corrosion resistance level is determined to be C (moderate corrosion); when R ct <2.5×10 3 Ω·cm 2 E corr <-1.20 V, i corr >50 μA·cm -2 At that time, the overall corrosion resistance level was determined to be D (severe corrosion).
[0011] The grading standard provided by this invention enables a comprehensive and quantitative evaluation of the density and corrosion resistance of additive manufacturing aluminum alloys, effectively distinguishing the quality grades of materials from different processes or batches, and providing a reliable basis for process optimization and quality control.
[0012] In the above technical solution, in step (1), the surface roughness R of the additively manufactured aluminum alloy sample is... a ≤0.1 μm.
[0013] In the above technical solution, in step (1), the aluminum alloy to be tested in additive manufacturing is one of AlSi alloy, AlMg alloy or AlMn alloy.
[0014] In the above technical solution, in step (1), the additively manufactured aluminum alloy sample to be tested is ultrasonically cleaned in acetone, anhydrous ethanol, and deionized water for 10-15 min respectively; dried, and then encapsulated using epoxy resin cold mounting, exposing only a 1.0 cm² area. 2 The plane is used as the working electrode.
[0015] In the above technical solution, in step (1), the sodium sulfate (Na2SO4) electrolyte includes a basic solution and sodium sulfate with a concentration of 0.1±0.05 mol / L; the sodium chloride (NaCl) electrolyte includes a basic solution and sodium chloride with a concentration of 0.1±0.05 mol / L; the sodium fluoride (NaF) electrolyte includes a basic solution and sodium fluoride with a concentration of 0.1±0.05 mol / L; wherein, by mass fraction, the basic solution includes the following components: acetic acid 10%~15%, sodium acetate 20%~25%, glycerol 2%~7%, and 2-propanol 5%~10%.
[0016] The sodium sulfate electrolyte described in this invention simulates a neutral oxygen-containing environment, where sulfate ions exhibit weak corrosiveness. It is primarily used to evaluate the intrinsic ability of materials to form a stable passivation film and their tendency for uniform corrosion. The response in this environment can indirectly reflect the chemical homogeneity of the material surface and the density of the near-surface layer.
[0017] The sodium chloride electrolyte described in this invention simulates a typical chloride ion corrosion environment and is used to assess the susceptibility of materials to localized corrosion. The occurrence of corrosion is closely related to active sites such as surface defects, inclusions, and pores.
[0018] The sodium fluoride electrolyte described in this invention simulates a special chemical environment containing fluoride ions. Fluoride ions have a strong complexing and dissolving effect on aluminum alloy oxide films, and can rapidly destroy the passivation film. Behavior in this environment can sensitively reflect the overall stability of the passivation film and the substrate's ability to resist rapid and uniform dissolution, and is related to the overall density of the material and the distribution of alloying elements.
[0019] Furthermore, the electrolyte of the present invention is prepared using analytical grade reagents and ultrapure water, and the temperature is precisely controlled at 25.0±0.5°C in a constant temperature bath.
[0020] In the above technical solution, the open-circuit potential monitoring includes: real-time monitoring of the open-circuit potential of the working electrode until its rate of change with time is less than 0.1 mV / min, so that the system reaches a quasi-steady state.
[0021] In the above technical solution, the frequency range of the electrochemical impedance spectroscopy test is 100 kHz to 10 mHz, and the sine wave amplitude is 10 mV.
[0022] In the above technical solution, the starting potential for the potentiodynamic polarization curve test is -1 to 0.5 V, the scan rate is 0.1 to 1 mV / s, and it terminates when the anodic current density reaches 1 mA / cm². 2 .
[0023] Furthermore, for each electrolyte, the following standardized testing sub-procedure is performed: Open circuit potential monitoring: Connect to an electrochemical workstation to monitor the open circuit potential of the working electrode in real time until its rate of change over time is less than 0.1 mV / min, so that the system reaches a quasi-steady state.
[0024] Electrochemical impedance spectroscopy (EIS) was performed at the stable open-circuit potential described above, measuring the impedance response over a wide frequency range (100 kHz to 10 mHz). Information regarding the electrode / solution interface double layer, surface film (passivation film) resistance, charge transfer processes, and potential mass transport was obtained via EIS.
[0025] Potentiodynamic polarization curve test: After completing EIS, immediately start the potentiodynamic scanning. The scan ranges from -1 to 0.5 V, with a step height of 2 mV, a step time of 1 s, and a scan rate of 0.002 V / s, scanning slowly in the positive direction until the current rises significantly or reaches the preset upper limit of the anode potential.
[0026] In the above technical solution, after completing all electrochemical measurements in one electrolyte, the sample is removed and immediately rinsed thoroughly with running ultrapure water for at least 60 seconds. It is then ultrasonically cleaned in fresh ultrapure water for several minutes and finally dried. This step is crucial to prevent cross-contamination of different electrolyte components, aiming to provide a "clean" surface condition for the next test—a surface that has undergone the previous reaction but has been free of foreign electrolytes—ensuring relative consistency of the starting conditions for each test.
[0027] The beneficial effects of this invention are: (1) The present invention uses the same additively manufactured aluminum alloy sample to conduct electrochemical tests in sodium sulfate, sodium chloride and sodium fluoride electrolytes in sequence. It can obtain response information under multiple corrosive environments on the same microstructure entity, avoid data fluctuations caused by differences in structure, porosity and density between different samples, and improve the comparability and reliability of test results.
[0028] (2) The present invention extracts the charge transfer resistance R in sodium sulfate electrolyte. ct The self-corrosion potential E in sodium chloride electrolyte corr and the corrosion current density i in sodium fluoride electrolyte corr A set of characteristic electrochemical parameters was constructed, which can reflect the passivation film stability, pitting corrosion resistance and uniform corrosion resistance of the material, respectively, and realize the correlation evaluation between the internal quality and corrosion resistance of additively manufactured aluminum alloys.
[0029] (3) The present invention establishes a grade evaluation method based on electrochemical parameters, which can quantitatively determine the density grade, corrosion resistance grade and comprehensive corrosion resistance grade of additive manufacturing aluminum alloys, and provides a unified standard for quality evaluation of different process parameters, different batches or different material systems.
[0030] (4) Compared with traditional metallographic observation, Archimedes method or salt spray test, the test process of the present invention is relatively fast, the sample damage is small, and there is no need to prepare multiple samples for density and corrosion performance testing, which reduces the test cost and improves the evaluation efficiency. It is suitable for batch screening and process optimization of additive manufacturing aluminum alloy components.
[0031] (5) The present invention can quickly screen out the preferred forming process window with high density and high corrosion resistance based on the comprehensive level, providing an effective basis for optimizing process parameters, quality control and reliability evaluation of engineering applications of additive manufacturing aluminum alloy materials. Attached Figure Description
[0032] Figure 1 This is a flowchart illustrating the overall evaluation method of the present invention.
[0033] Figure 2 The electrochemical impedance spectroscopy of sample M1 in Example 2 in a solution of 0.1 mol / L Na2SO4, NaCl, and NaF as ion transport agents is shown.
[0034] Figure 3 The graph shows the potentiodynamic polarization curve of the fixed sample M1 in Example 2 in a solution of 0.1 mol / L Na2SO4, NaCl, and NaF as ion transport agents.
[0035] Figure 4The electrochemical impedance spectroscopy of sample M2 in Example 2 in a solution of 0.1 mol / L Na2SO4, NaCl, and NaF as ion transport agents is shown.
[0036] Figure 5 The graph shows the potentiodynamic polarization curves of the fixed sample M2 in Example 2 in a solution of 0.1 mol / L Na2SO4, NaCl, and NaF as ion transport agents.
[0037] Figure 6 The electrochemical impedance spectroscopy of sample M3 in Example 2 in a solution of 0.1 mol / L Na2SO4, NaCl, and NaF as ion transport agents is shown.
[0038] Figure 7 The graph shows the potentiodynamic polarization curves of the fixed sample M3 in Example 2 in a solution of 0.1 mol / L Na2SO4, NaCl, and NaF as ion transport agents.
[0039] Figure 8 Metallographic images of the fixed samples M1, M2, and M3 in Example 2. Detailed Implementation
[0040] The following non-limiting embodiments are intended to enable those skilled in the art to more fully understand the invention, but do not limit the invention in any way.
[0041] Unless otherwise specified, the experimental methods described in the following examples are conventional methods; the reagents and materials described are commercially available unless otherwise specified.
[0042] The following examples use AlMn-based alloys as an example to illustrate in detail the method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys based on single-sample multi-electrolyte electrochemical testing provided by this invention. However, those skilled in the art should understand that this method is also applicable to other series of aluminum alloys, such as AlSi, AlMg, and AlCu alloys.
[0043] Example 1 This embodiment proposes a three-level characteristic electrochemical parameter classification standard based on the distribution law of measured data of samples prepared with different process parameters, and in combination with density testing and electrochemical corrosion behavior. The specific steps include the following: (1) Preparation of additive manufacturing aluminum alloy samples based on different process parameters Aluminum alloy samples with dimensions of 15 mm × 15 mm × 15 mm were prepared by selective laser melting (SLM) using gas-atomized AlMn alloy powder under different process parameters.
[0044] (2) Electrolyte preparation and testing Sodium sulfate (Na₂SO₄) electrolyte: comprising a base solution and sodium sulfate at a concentration of 0.1 mol / L; Sodium chloride (NaCl) electrolyte: comprising a base solution and sodium chloride at a concentration of 0.1 mol / L; Sodium fluoride (NaF) electrolyte: comprising a base solution and sodium fluoride at a concentration of 0.1 mol / L; wherein, by mass fraction, the base solution comprises the following components: acetic acid 12%, sodium acetate 22%, glycerol 5%, 2-propanol 8%, and the balance being ultrapure water. The electrolytes are prepared using ultrapure water and analytical grade reagents, and the electrolyte temperature is maintained at 25.0℃.
[0045] Using a DH7000C electrochemical workstation with a three-electrode system, additively manufactured aluminum alloy samples of 10 mm × 10 mm × 2 mm were cut out, ensuring that the working surface (parallel to the substrate) represented the main structure of the material. The samples were then ultrasonically cleaned sequentially in acetone and anhydrous ethanol for 15 min each, rinsed with deionized water, and dried. Epoxy resin cold mounting was used, precisely controlling the exposed working area to be 1.0 cm². 2 The working electrode was a graphite electrode, and the reference electrode was a saturated calomel electrode (SCE). The tests were strictly performed in the order of Na₂SO₄ electrolyte → NaCl electrolyte → NaF electrolyte. Throughout the test, the sample remained constant; the only variable was the chemical composition of the electrolyte. For each electrolyte, the following standardized test sub-procedure was executed: a. Open circuit potential monitoring: Connect to an electrochemical workstation to monitor the open circuit potential of the working electrode in real time until its rate of change over time is less than 0.1 mV / min, so that the system reaches a quasi-steady state.
[0046] b. Electrochemical Impedance Spectroscopy (EIS): At the stable open-circuit potential described above, the impedance response was measured over a wide frequency range of 100 kHz to 10 mHz with a sinusoidal amplitude of 10 mV. Information regarding the electrode / solution interface double layer, surface film (passivation film) resistance, charge transfer processes, and possible mass transport was obtained via EIS.
[0047] c. Potentiodynamic polarization curve test: Immediately after completing EIS, start the potentiodynamic scanning. The scan starts at -250 mV, with a step height of 2 mV, a step time of 1 s, and a scan rate of 0.002 V / s, slowly scanning in the positive direction, terminating when the anodic current density reaches 1 mA / cm². 2 .
[0048] d. After completing all electrochemical measurements in one electrolyte, remove the sample and immediately rinse the working surface thoroughly with running ultrapure water for at least 60 seconds. Then, ultrasonically clean it in fresh ultrapure water for several minutes, and finally dry it. This step is crucial to prevent cross-contamination between different electrolyte components and aims to provide a "clean" surface condition for the next test, free of foreign electrolytes despite previous reactions, ensuring relative consistency of starting conditions for each test.
[0049] The extracted key parameters were tested sequentially in three electrolytes, including: The charge transfer resistance (R) measured in an electrolyte using Na2SO4 as an ion transporter ct ): Reflects the density and stability of the passivation film on the material surface, and is highly correlated with the overall density; The self-corrosion potential (E) measured in an electrolyte with NaCl as the ion transporter corr The potential (α) characterizes the sensitivity of a material to chloride ion-induced pitting corrosion; the more positive the potential, the stronger the resistance to localized corrosion. Corrosion current density (i) measured in an electrolyte with NaF as the ion transporter corr : Characterizes the uniform dissolution rate of a material in a highly corrosive fluoride ion environment. The smaller the value, the better the overall density and resistance to uniform corrosion of the material.
[0050] To propose a three-level classification standard for characteristic electrochemical parameters, the additively manufactured aluminum alloy samples prepared based on different process parameters were tested as follows: (1) Salt spray test method Salt spray test results show that: Grade A corrosion resistance corresponds to no corrosion on the surface, Grade B corresponds to slight corrosion, Grade C corresponds to moderate corrosion, and Grade D corresponds to severe corrosion.
[0051] (2) Density test The density of each sample was measured using the Archimedes displacement method. Each sample was measured three times and the average value was taken. The density test results showed that: Grade A corresponds to a density ≥99.60%, Grade B corresponds to 99.50% ≤ density <99.60%, Grade C corresponds to 99.00% ≤ density <99.50%, and Grade D corresponds to a density <99.00%.
[0052] (3) Mechanical property testing Miniature tensile specimens conforming to ASTM E8 standards (gauge length 10 mm, width 2 mm) were cut (3 parallel specimens for each parameter). Tensile tests were conducted at room temperature at a tensile rate of 1 mm / min, and the tensile strength and elongation after fracture were recorded. The mechanical property test results showed that: for tensile strength, Grade A corresponds to a tensile strength ≥ 460 N / m², Grade B corresponds to 450 N / m² ≤ < 460 N / m², Grade C corresponds to 400 N / m² ≤ < 450 N / m², and Grade D corresponds to < 400 N / m²; for elongation, Grade A corresponds to an elongation ≥ 17.0 N / m², Grade B corresponds to 16.0 N / m² ≤ < 17.0 N / m², Grade C corresponds to 15.0 N / m² ≤ < 16.0 N / m², and Grade D corresponds to < 15.0 N / m².
[0053] Based on the distribution pattern of the above measured data, the charge transfer resistance R is... ct Self-corrosion potential E corr Corrosion current density i corr The test results for the three parameters are divided into four levels: A, B, C, and D. The threshold ranges for each level are as follows: When R ct ≥8.0×10 3 Ω·cm 2 When the corrosion resistance is 5.0 × 10⁻⁶, the corrosion resistance grade is determined to be Grade A; when the corrosion resistance is 5.0 × 10⁻⁶, the corrosion resistance grade is determined to be Grade A. 3 ≤R ct <8.0×10 3 Ω·cm 2 When the corrosion resistance is 2.5 × 10⁻⁶, the corrosion resistance grade is determined to be B; when the corrosion resistance is 2.5 × 10⁻⁶, the corrosion resistance grade is determined to be B. 3 ≤R ct <5.0×10 3 Ω·cm 2 When R is present, the corrosion resistance grade is determined to be C; when R is present, the corrosion resistance grade is determined to be C. ct <2.5×10 3 Ω·cm 2 At that time, the corrosion resistance level was determined to be Grade D; The self-corrosion potential E corr It is positively correlated with corrosion resistance, i.e., E corr The higher the positive value, the stronger the corrosion resistance; according to the self-corrosion potential E... corr Corrosion resistance rating: When E corr When the corrosion resistance is ≥-0.80 V, the corrosion resistance grade is determined to be Class A; when -1.05 ≤ E corr When the voltage is less than -0.80 V, the corrosion resistance grade is determined to be B; when -1.20 ≤ E corr When the temperature is < -1.05 V, the corrosion resistance grade is determined to be C; when the temperature is < -1.05 V, the corrosion resistance grade is determined to be C. corr When the voltage is less than -1.20 V, the corrosion resistance grade is determined to be D. The corrosion current density i corr It is negatively correlated with corrosion resistance, i. corrThe smaller the value, the stronger the corrosion resistance; according to the corrosion current density i corr Corrosion resistance rating: When i corr ≤25.0 μA·cm -2 When 25 < i, the corrosion resistance grade is determined to be Grade A; when 25 < i corr ≤37 μA·cm -2 When 37 < i, the uniform corrosion resistance grade is determined to be B; corr ≤50 μA·cm -2 When the corrosion resistance is determined to be grade C; when i corr >50 μA·cm -2 At that time, the corrosion resistance level was determined to be Grade D; According to the above R ct E corr and i corr The overall corrosion resistance rating is determined by assessing the three individual ratings according to the following rules: When the Rct grade is A, the icorr grade is A, and the Ecorr grade is not lower than B, the overall corrosion resistance grade is determined to be A. When the conditions for Grade A are not met, but all three individual grades are not lower than Grade B, the overall corrosion resistance grade is determined to be Grade B. When all three individual grades are not lower than Grade C, and at least one individual grade is Grade C, the overall corrosion resistance grade is determined to be Grade C. When any single item is rated D, the overall corrosion resistance rating is determined to be D. The corrosion resistance rating is as follows: Grade A corresponds to no corrosion on the surface, Grade B corresponds to slight corrosion, Grade C corresponds to moderate corrosion, and Grade D corresponds to severe corrosion.
[0054] When the overall corrosion resistance grade is A, the corresponding density grade is A, i.e., density ≥ 99.60%; when the overall corrosion resistance grade is B, the corresponding density grade is B, i.e., 99.50% ≤ density < 99.60%; when the overall corrosion resistance grade is C, the corresponding density grade is C, i.e., 99.00% ≤ density < 99.50%; when the overall corrosion resistance grade is D, the corresponding density grade is D, i.e., density < 99.00%.
[0055] Example 2 This embodiment aims to demonstrate how to use the method of the present invention to systematically test multiple additive manufacturing aluminum alloy samples prepared with different selective laser melting (SLM) process parameters. By extracting characteristic electrochemical parameters and combining them with tensile property test results, a quantitative correlation between electrochemical response and material density and mechanical properties is established, and the effectiveness of the proposed rating criteria is verified.
[0056] A method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys, comprising the following steps: 1. Preparation of fixed samples Material: Gas-atomized AlMn alloy powder.
[0057] Process: Laser selective melting technology was used to prepare AlMn-based aluminum alloy samples 1, 2 and 3, with sample dimensions of 15 mm × 15 mm × 15 mm; the specific process parameters are shown in Table 1.
[0058] Sampling and processing: Cut out 10 mm 10 mm For 2 mm samples, ensure the working surface (parallel to the substrate) represents the main material structure. The samples were ultrasonically cleaned sequentially in acetone and anhydrous ethanol for 15 minutes each, rinsed with deionized water, and dried. Epoxy resin cold mounting was used, precisely controlling the exposed working area to be 1.0 cm². 2 The samples are designated as samples M1, M2, and M3, respectively.
[0059] Table 1 Selective laser melting process parameters for the samples
[0060] 2. Electrolyte preparation and testing The electrochemical testing procedures for M1, M2, and M3 were the same as in Example 1, and their response characteristics in the three electrolytes were obtained. The results are shown in […]. Figures 2-7 .
[0061] Electrochemical impedance spectroscopy (EIS) results: In the solution using NaCl as the ion transporter, the Nyquist plot showed a large-radius capacitive arc, indicating high interfacial impedance and a relatively stable passivation film. In the solution using Na₂SO₄ as the ion transporter, the capacitive arc radius decreased significantly, revealing that SO₄²⁻… 2- The adsorption and erosion of the surface film by ions. In the solution using NaF as the ion transporter, the capacitive arc shrinks to an extremely small size, which directly reflects the strong destructive effect of fluoride ions on the alumina passivation film, resulting in extremely low interfacial resistance.
[0062] Results of potentiodynamic polarization curves: In NaCl solution with ion transport, the curve shows a broad and stable passivation region with extremely low self-corrosion current density. In Na2SO4 solution with ion transport, the passivation region narrows. In NaF solution with ion transport, almost no obvious passivation region is observed, the self-corrosion potential shifts negatively, and the corrosion current density increases significantly, indicating that rapid and comprehensive corrosion has occurred in the material.
[0063] Based on the above test results, key electrochemical parameters that most sensitively reflect the internal density and different corrosion behaviors of the material were extracted from the responses of various electrolyte environments, and a "characteristic electrochemical parameter set" for the sample was constructed. From the EIS data of the Na2SO4 ion transport solution, the charge transfer resistance (Rc) characterizing the charge transfer resistance was obtained using equivalent circuit fitting. ct Extracted from the polarization curves of NaCl-based solutions: the critical potential for a sharp increase in anodic current, i.e., the self-corrosion potential E, was determined. corr The more positive the potential, the stronger the material's resistance to chloride-induced localized corrosion. Extracted from the polarization curves of NaF solutions using ion transporters, the self-corrosion current density i was calculated using Tafel extrapolation. corr The self-corrosion current density directly reflects the rate at which the matrix of the material undergoes uniform dissolution in a highly corrosive fluoride ion environment. The lower the value, the better the overall corrosion resistance and density of the material.
[0064] Therefore, the characteristic electrochemical parameter set of the sample can be quantified into a set containing three key parameters, the results of which are shown in Table 2: In the solution with Na2SO4 as the ion transport agent, the charge transfer resistance R was obtained by fitting EIS data (using the equivalent circuit of R(Q(R(QR)))). ct In a solution using NaCl as the ion transporter, the self-corrosion potential E is determined from the potentiodynamic polarization curve. corr In a solution using NaF as the ion transporter, the corrosion current density i was obtained by Tafel extrapolation. corr .
[0065] 3. Correlation analysis between electrochemical parameters and density and tensile properties To verify the effectiveness of the evaluation method in Example 1, mechanical property tests and density tests were also conducted on the aluminum alloy samples from Example 1, following the same testing procedures as in Example 1. The results of characteristic electrochemical parameter tests, density tests, and tensile property tests for each sample are shown in Table 2.
[0066] Table 2 Density, tensile properties, and characteristic electrochemical parameters of samples with different process parameters
[0067] As can be seen from the data in Table 2, the sample M2 (99.6%) with the highest density exhibited the highest charge transfer resistance (8.33 × 10⁻⁶) in the Na₂SO₄ ion transport solution. 4 Ω·cm 2 The corrosion potential is relatively high (-1.01 V) in NaCl solution with ion transporter, and the corrosion current density is the lowest (23.09 × 10⁻⁶ V) in NaF solution with ion transporter. -6 A / cm 2This indicates the best passivation film stability and corrosion resistance. As the density decreases, all three electrochemical parameters show a deterioration trend: R... ct Significantly reduced, E corr Negative shift, i corr The increase indicates that the increase in defects such as pores within the material directly leads to the deterioration of its electrochemical behavior.
[0068] The tensile properties (tensile strength and elongation) are highly consistent with the density and electrochemical parameters, and the samples with high density also have excellent mechanical properties.
[0069] 4. Apply rating standards to conduct a comprehensive rating assessment. Based on the rating criteria established in Example 1, the electrochemical parameters of each sample were substituted to obtain the individual rating and the overall corrosion resistance rating, as shown in Table 3.
[0070] Table 3. Evaluation results of individual and overall corrosion resistance grades for each sample.
[0071] The rating results show that the overall corrosion resistance level perfectly corresponds to the measured density: Grade A corresponds to a density ≥ 99.6%, Grade B corresponds to 99.50% ≤ density < 99.60%, and Grade C corresponds to 99.00% ≤ density < 99.50%. This indicates that the characteristic parameter set based on single-sample multi-electrolyte electrochemical testing proposed in this invention can effectively distinguish additive manufacturing aluminum alloy materials with different density levels.
[0072] By comparing the overall grades of samples with three different process parameters, it is clear that a process window using 190 W laser power and a scanning speed of 900 mm / s can produce Grade A materials with the highest density, best corrosion resistance, and optimal tensile properties. Therefore, the method of this invention can quickly guide the optimization of process parameters and screen out the optimal process window for obtaining high-density, high-corrosion-resistant materials.
[0073] This embodiment verifies the effectiveness of the method of the present invention in the quality assessment of additive manufacturing aluminum alloys. By performing fixed-sample multi-electrode tests on samples from the same series of different processes, the extracted characteristic electrochemical parameter set showed a strong correlation with the material density and tensile properties. The established rating standard can reliably classify the comprehensive performance of the material, providing a rapid and minimally destructive assessment method for process screening and batch quality determination.
Claims
1. A method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys, characterized in that: Includes the following steps: (1) The aluminum alloy sample to be tested in additive manufacturing is packaged and used as the working electrode, which together with the graphite counter electrode and the saturated calomel reference electrode constitutes a three-electrode system. The sample was sequentially immersed in sodium sulfate electrolyte, sodium chloride electrolyte, and sodium fluoride electrolyte. In each electrolyte, open-circuit potential monitoring, electrochemical impedance spectroscopy, and potentiodynamic polarization curve testing were performed sequentially; the working electrode surface was cleaned and dried after each test. (2) Extract characteristic electrochemical parameters from the test data obtained in step (1) to form a characteristic electrochemical parameter set for the sample. The characteristic electrochemical parameter set includes: the charge transfer resistance R measured in sodium sulfate electrolyte. ct The self-corrosion potential E measured in sodium chloride electrolyte corr Corrosion current density i measured in sodium fluoride electrolyte corr The overall corrosion resistance level of the material represented by the sample is evaluated based on this set of characteristic electrochemical parameters. (3) Based on the comprehensive corrosion resistance grade obtained from the evaluation, further evaluate the density grade of the material represented by the sample. The higher the comprehensive corrosion resistance grade, the higher the density grade and the larger the density value.
2. The method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys according to claim 1, characterized in that: In step (2), the characteristic electrochemical parameter set and the overall corrosion resistance have the following quantitative correlation: The charge transfer resistor R ct It is positively correlated with corrosion resistance: when R ct ≥8.0×10 3 Ω·cm 2 When the corrosion resistance is 5.0 × 10⁻⁶, the corrosion resistance grade is determined to be Grade A; when the corrosion resistance is 5.0 × 10⁻⁶, the corrosion resistance grade is determined to be Grade A. 3 ≤R ct <8.0×10 3 Ω·cm 2 When the corrosion resistance is 2.5 × 10⁻⁶, the corrosion resistance grade is determined to be B; when the corrosion resistance is 2.5 × 10⁻⁶, the corrosion resistance grade is determined to be B. 3 ≤R ct <5.0×10 3 Ω·cm 2 When R is present, the corrosion resistance grade is determined to be C; when R is present, the corrosion resistance grade is determined to be C. ct <2.5×10 3 Ω·cm 2 At that time, the corrosion resistance level was determined to be Grade D; The self-corrosion potential E corr It is positively correlated with corrosion resistance: when E corr When the corrosion resistance is ≥-0.80 V, the corrosion resistance grade is determined to be Class A; when -1.05 ≤ E corr When the voltage is less than -0.80 V, the corrosion resistance grade is determined to be B; when -1.20 ≤ E corr When the temperature is <-1.05 V, the corrosion resistance grade is determined to be C; when the temperature is <-1.05 V, the corrosion resistance grade is determined to be C. corr When the voltage is less than -1.20 V, the corrosion resistance grade is determined to be D. The corrosion current density i corr It is negatively correlated with corrosion resistance: when i corr ≤25.0 μA·cm -2 When 25 < i, the corrosion resistance grade is determined to be Grade A; when 25 < i corr ≤37 μA·cm -2 When 37 < i, the corrosion resistance grade is determined to be B; corr ≤50 μA·cm -2 When the corrosion resistance is determined to be grade C; when i corr >50 μA·cm -2 At that time, the corrosion resistance level was determined to be Grade D; According to the above R ct E corr and i corr The overall corrosion resistance rating is determined by assessing the three individual ratings according to the following rules: When R ct Grade A, i corr Grade A, and E corr When the grade is not lower than B, the overall corrosion resistance grade is determined to be A. When the conditions for Grade A are not met, but all three individual grades are not lower than Grade B, the overall corrosion resistance grade is determined to be Grade B. When all three individual grades are not lower than Grade C, and at least one individual grade is Grade C, the overall corrosion resistance grade is determined to be Grade C. When any single item is rated D, the overall corrosion resistance rating is determined to be D. Grade A corresponds to no corrosion on the surface, Grade B corresponds to slight corrosion, Grade C corresponds to moderate corrosion, and Grade D corresponds to severe corrosion.
3. The method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys according to claim 2, characterized in that: When the overall corrosion resistance grade is A, the corresponding density grade is A, i.e., density ≥ 99.60%; when the overall corrosion resistance grade is B, the corresponding density grade is B, i.e., 99.50% ≤ density < 99.60%; when the overall corrosion resistance grade is C, the corresponding density grade is C, i.e., 99.00% ≤ density < 99.50%; when the overall corrosion resistance grade is D, the corresponding density grade is D, i.e., density < 99.00%.
4. The method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys according to claim 1, characterized in that: In step (1), the surface roughness R of the additively manufactured aluminum alloy sample to be tested is... a ≤0.1 μm.
5. The method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys according to claim 1, characterized in that: In step (1), the aluminum alloy to be tested for additive manufacturing is one of AlSi alloy, AlMg alloy or AlMn alloy.
6. The method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys according to claim 1, characterized in that: In step (1), the additively manufactured aluminum alloy sample to be tested is ultrasonically cleaned in acetone, anhydrous ethanol, and deionized water for 10-15 min respectively; dried, and then encapsulated using epoxy resin cold mounting, exposing only a 1.0 cm² area. 2 The plane is used as the working electrode.
7. The method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys according to claim 1, characterized in that: In step (2), the sodium sulfate electrolyte comprises a base solution and sodium sulfate with a concentration of 0.1±0.05 mol / L; the sodium chloride electrolyte comprises a base solution and sodium chloride with a concentration of 0.1±0.05 mol / L; the sodium fluoride electrolyte comprises a base solution and sodium fluoride with a concentration of 0.1±0.05 mol / L; wherein, by mass fraction, the base solution comprises the following components: acetic acid 10%~15%, sodium acetate 20%~25%, glycerol 2%~7%, and 2-propanol 5%~10%.
8. The method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys according to claim 1, characterized in that: In step (2), the open-circuit potential monitoring includes: real-time monitoring of the open-circuit potential of the working electrode until its rate of change with time is less than 0.1 mV / min, so that the system reaches a quasi-steady state.
9. The method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys according to claim 1, characterized in that: In step (2), the frequency range of the electrochemical impedance spectroscopy test is 100 kHz to 10 mHz, and the amplitude of the sine wave is 10 mV.
10. The method for evaluating the correlation between density and corrosion resistance of additively manufactured aluminum alloys according to claim 1, characterized in that: In step (2), the starting potential for the potentiodynamic polarization curve test is -1 to 0.5 V, the scan rate is 0.1 to 1 mV / s, and it terminates when the anode current density reaches 1 mA / cm². 2 .
Citation Information
Patent Citations
Electrolyte solution for electrolytic corrosion of cobalt-chromium alloy for 3D printing, and electrolysis method
CN113481583A
Material gene design method and laser additive manufacturing preparation method of novel high-toughness corrosion-resistant aluminum alloy
CN116904813A